Open Access

Some results for high-order generalized neutral differential equation

Advances in Difference Equations20132013:202

https://doi.org/10.1186/1687-1847-2013-202

Received: 3 April 2013

Accepted: 20 June 2013

Published: 8 July 2013

Abstract

In this paper, we consider the following high-order p-Laplacian generalized neutral differential equation

( φ p ( x ( t ) c x ( t δ ( t ) ) ) ) ( n 1 ) + g ( t , x ( t ) , x ( t τ ( t ) ) , x ( t ) ) = e ( t ) ,

where p 2 , φ p ( x ) = | x | p 2 x for x 0 and φ p ( 0 ) = 0 ; g : R 4 R is a continuous periodic function with g ( t + T , , , ) g ( t , , , ) , and g ( t , a , a , 0 ) e ( t ) 0 for all a R . e : R R is a continuous periodic function with e ( t + T ) e ( t ) and 0 T e ( t ) d t = 0 , c is a constant and | c | 1 , δ C 1 ( R , R ) and δ is a T-periodic function, T is a positive constant; n is a positive integer. By applications of coincidence degree theory and some analysis skills, sufficient conditions for the existence of periodic solutions are established.

MSC:34K13, 34K40, 34C25.

Keywords

periodic solutionhigh-ordergeneralized neutral differential equation

1 Introduction

In recent years, there has been a good amount of work on periodic solutions for neutral differential equations (see [19] and the references cited therein). For example, in [1], Cao and He investigated a class of high-order neutral differential equations
( x ( p ) ( t ) + b p x ( p ) ( t h p ) ) + i = 0 p 1 ( a i x ( i ) + b i x ( i ) ( t h i ) ) = f ( t ) .
(1.1)
By using the Fourier series method and inequality technique, they obtained the existence of a periodic solution for (1.1). In [8], applying Mawhin’s continuation theorem, Wang and Lu studied the existence of a periodic solution for a high-order neutral functional differential equation with distributed delay as follows:
( x ( t ) c x ( t σ ) ) ( n ) + f ( x ( t ) ) x ( t ) + g ( r 0 x ( t + s ) d α ( s ) ) = p ( t ) ,
(1.2)
here | c | 1 . Recently, in [5] and [6], Ren et al. observed the high-order p-Laplacian neutral differential equation
( φ p ( x ( t ) c x ( t σ ) ) ( l ) ) ( n l ) = F ( t , x ( t ) , x ( t ) , , x ( l 1 ) ( t ) )
(1.3)

and presented sufficient conditions for the existence of periodic solutions for (1.3) in the critical case (i.e., | c | = 1 ) and in the general case (i.e., | c | 1 ), respectively.

In this paper, we consider the following high-order p-Laplacian generalized neutral differential equation
( φ p ( x ( t ) c x ( t δ ( t ) ) ) ) ( n 1 ) + g ( t , x ( t ) , x ( t τ ( t ) ) , x ( t ) ) = e ( t ) ,
(1.4)

where p 2 , φ p ( x ) = | x | p 2 x for x 0 and φ p ( 0 ) = 0 ; g : R 4 R is a continuous periodic function with g ( t + T , , , ) g ( t , , , ) , and g ( t , a , a , 0 ) e ( t ) 0 for all a R . e : R R is a continuous periodic function with e ( t + T ) e ( t ) and 0 T e ( t ) d t = 0 , c is a constant and | c | 1 , δ C 1 ( R , R ) and δ is a T-periodic function, T is a positive constant; n is a positive integer.

In (1.4), the neutral operator A = x ( t ) c x ( t δ ( t ) ) is a natural generalization of the operator A 1 = x ( t ) c x ( t δ ) , which typically possesses a more complicated nonlinearity than A 1 . For example, A 1 is homogeneous in the following sense ( A 1 x ) ( t ) = ( A 1 x ) ( t ) , whereas A in general is inhomogeneous. As a consequence, many of the new results for differential equations with the neutral operator A will not be a direct extension of known theorems for neutral differential equations.

The paper is organized as follows. In Section 2, we first give qualitative properties of the neutral operator A which will be helpful for further studies of differential equations with this neutral operator; in Section 3, by applying Mawhin’s continuation theory and some new inequalities, we obtain sufficient conditions for the existence of periodic solutions for (1.4), an example is also given to illustrate our results.

2 Lemmas

Let C T = { ϕ C ( R , R ) : ϕ ( t + T ) ϕ ( t ) } with the norm | ϕ | = max t [ 0 , T ] | ϕ ( t ) | . Define difference operators A and B as follows:
A : C T C T , ( A x ) ( t ) = x ( t ) c x ( t δ ( t ) ) ; B : C T C T , ( B x ) ( t ) = c ( t δ ( t ) ) .

Lemma 2.1 (see [10])

If | c | 1 , then the operator A has a continuous inverse A 1 on C T , satisfying
(1) ( A 1 f ) ( t ) = { f ( t ) + j = 1 c j f ( s i = 1 j 1 δ ( D i ) ) for | c | < 1 , f C T , f ( t + δ ( t ) ) c j = 1 1 c j + 1 f ( s + δ ( t ) + i = 1 j 1 δ ( D i ) ) for | c | > 1 , f C T . (2) | ( A 1 f ) ( t ) | f | 1 | c | | , f C T . (3) 0 T | ( A 1 f ) ( t ) | d t 1 | 1 | c | | 0 T | f ( t ) | d t , f C T .

Let X and Y be real Banach spaces and let L : D ( L ) X Y be a Fredholm operator with index zero, here D ( L ) denotes the domain of L. This means that ImL is closed in Y and dim Ker L = dim ( Y / Im L ) < + . Consider supplementary subspaces X 1 , Y 1 of X, Y respectively such that X = Ker L X 1 , Y = Im L Y 1 . Let P : X Ker L and Q : Y Y 1 denote the natural projections. Clearly, Ker L ( D ( L ) X 1 ) = { 0 } and so the restriction L P : = L | D ( L ) X 1 is invertible. Let K denote the inverse of L P .

Let Ω be an open bounded subset of X with D ( L ) Ω . A map N : Ω ¯ Y is said to be L-compact in Ω ¯ if Q N ( Ω ¯ ) is bounded and the operator K ( I Q ) N : Ω ¯ X is compact.

Lemma 2.2 (Gaines and Mawhin [11])

Suppose that X and Y are two Banach spaces, and L : D ( L ) X Y is a Fredholm operator with index zero. Let Ω X be an open bounded set and N : Ω ¯ Y be L-compact on Ω ¯ . Assume that the following conditions hold:
  1. (1)

    L x λ N x , x Ω D ( L ) , λ ( 0 , 1 ) ;

     
  2. (2)

    N x Im L , x Ω Ker L ;

     
  3. (3)

    deg { J Q N , Ω Ker L , 0 } 0 , where J : Im Q Ker L is an isomorphism.

     

Then the equation L x = N x has a solution in Ω ¯ D ( L ) .

Lemma 2.3 (see [12])

If x C n ( R , R ) and x ( t + T ) x ( t ) , then
0 T | x ( t ) | p d t ( T π p ) p ( n 1 ) 0 T | x ( n ) ( t ) | p d t ,
(2.1)

where π p = 2 0 ( p 1 ) / p d s ( 1 s p p 1 ) 1 / p = 2 π ( p 1 ) 1 / p p sin ( π / p ) , and p is a fixed real number with p > 1 .

Remark 2.1 When p = 2 , π 2 = 2 0 ( 2 1 ) / 2 d s ( 1 s 2 2 1 ) 1 / 2 = 2 π ( 2 1 ) 1 / 2 2 sin ( π / 2 ) = π , then (2.1) is transformed into 0 T | x ( t ) | 2 d t ( T π ) 2 ( n 1 ) 0 T | x ( n ) ( t ) | 2 d t .

In order to apply Mawhin’s continuation degree theorem, we rewrite (1.4) in the form
{ ( A x 1 ) ( t ) = φ q ( x 2 ( t ) ) x 2 ( n 1 ) ( t ) = g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + e ( t ) ,
(2.2)

where 1 p + 1 q = 1 . Clearly, if x ( t ) = ( x 1 ( t ) , x 2 ( t ) ) is a T-periodic solution to (2.2), then x 1 ( t ) must be a T-periodic solution to (1.4). Thus, the problem of finding a T-periodic solution for (1.4) reduces to finding one for (2.2).

Now, set X = { x = ( x 1 ( t ) , x 2 ( t ) ) C ( R , R 2 ) : x ( t + T ) x ( t ) } with the norm | x | = max { | x 1 | , | x 2 | } ; Y = { x = ( x 1 ( t ) , x 2 ( t ) ) C 1 ( R , R 2 ) : x ( t + T ) x ( t ) } with the norm x = max { | x | , | x | } . Clearly, X and Y are both Banach spaces. Meanwhile, define
L : D ( L ) = { x C n ( R , R 2 ) : x ( t + T ) = x ( t ) , t R } X Y
by
( L x ) ( t ) = ( ( A x 1 ) ( t ) x 2 ( n 1 ) ( t ) )
and N : X Y by
( N x ) ( t ) = ( φ q ( x 2 ( t ) ) g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + e ( t ) ) .
(2.3)
Then (2.2) can be converted into the abstract equation L x = N x . From the definition of L, one can easily see that
Ker L R 2 , Im L = { y Y : 0 T ( y 1 ( s ) y 2 ( s ) ) d s = ( 0 0 ) } .
So, L is a Fredholm operator with index zero. Let P : X Ker L and Q : Y Im Q R 2 be defined by
P x = ( ( A x 1 ) ( 0 ) x 2 ( 0 ) ) ; Q y = 1 T 0 T ( y 1 ( s ) y 2 ( s ) ) d s ,
then Im P = Ker L , Ker Q = Im L . Setting L P = L | D ( L ) Ker P and L P 1 : Im L D ( L ) denotes the inverse of L P , then
[ L P 1 y ] ( t ) = ( ( A 1 G y 1 ) ( t ) ( G y 2 ) ( t ) ) , [ G y 1 ] ( t ) = 0 t y 1 ( s ) d s , [ G y 2 ] ( t ) = j = 1 n 2 1 j ! x 2 ( j ) ( 0 ) t j + 1 ( n 2 ) ! 0 t ( t s ) n 2 y 2 ( s ) d s ,
(2.4)
where x 2 ( j ) ( 0 ) ( j = 1 , 2 , , n 2 ) are defined by the following
B = ( 1 0 0 0 0 b 1 1 0 0 0 b 2 b 1 1 0 0 b n 3 b n 4 b n 5 1 0 b n 2 b n 3 b n 4 b 1 0 ) ( n 2 ) × ( n 2 ) , X = ( x ( n 2 ) ( 0 ) , , x ( 0 ) , x ( 0 ) ) , C = ( C 1 , C 2 , , C n 2 ) , C j = 1 j ! T 0 T ( T s ) j y 2 ( s ) d s , b k = T k ( k + 1 ) ! , k = 1 , 2 , , n 3 .

From (2.3) and (2.4), it is clear that QN and K ( I Q ) N are continuous, Q N ( Ω ¯ ) is bounded and then K ( I Q ) N ( Ω ¯ ) is compact for any open bounded Ω X which means N is L-compact on Ω ¯ .

3 Existence of periodic solutions for (1.4)

For the sake of convenience, we list the following assumptions which will be used repeatedly in the sequel:

(H1) There exists a constant D > 0 such that
v 1 g ( t , v 1 , v 2 , v 3 ) > 0 ( t , v 1 , v 2 , v 3 ) [ 0 , T ] × R 3  with  | v 1 | > D ;
(H2) There exists a constant D 1 > 0 such that
v 1 g ( t , v 1 , v 2 , v 3 ) < 0 ( t , v 1 , v 2 , v 3 ) [ 0 , T ] × R 3  with  | v 1 | > D 1 ;
(H3) There exist non-negative constants α 1 , α 2 , α 3 , m such that
| g ( t , v 1 , v 2 , v 3 ) | α 1 | v 1 | p 1 + α 2 | v 2 | p 1 + α 3 | v 3 | p 1 + m ( t , v 1 , v 2 , v 3 ) [ 0 , T ] × R 3 ;
(H4) There exist non-negative constants γ 1 , γ 2 , γ 3 such that
| g ( t , u 1 , u 2 , u 3 ) g ( t , v 1 , v 2 , v 3 ) | γ 1 | u 1 v 1 | + γ 2 | u 2 v 2 | + γ 3 | u 3 v 3 |

for all ( t , u 1 , u 2 , u 3 ) , ( t , v 1 , v 2 , v 3 ) [ 0 , T ] × R 3 .

Theorem 3.1 Assume that (H1) and (H3) hold, then (1.4) has at least one non-constant T-periodic solution if | 1 | c | | | c | δ 1 > 0 and [ ( α 1 + α 2 ) T p + 1 + 2 p 1 α 3 T 2 ] 2 p + 1 ( | 1 | c | | | c | δ 1 ) p 1 ( T π ) 2 ( n 3 ) < 1 , here δ 1 = max t [ 0 , T ] | δ ( t ) | .

Proof Consider the equation
L x = λ N x , λ ( 0 , 1 ) .
Set Ω 1 = { x : L x = λ N x , λ ( 0 , 1 ) } . If x ( t ) = ( x 1 ( t ) , x 2 ( t ) ) Ω 1 , then
{ ( A x 1 ) ( t ) = λ φ q ( x 2 ( t ) ) x 2 ( n 1 ) ( t ) = λ g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + λ e ( t ) .
(3.1)
Substituting x 2 ( t ) = λ 1 p φ p [ ( A x 1 ) ( t ) ] into the second equation of (3.1), we get
( φ p ( A x 1 ) ( t ) ) ( n 1 ) + λ p g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) = λ p e ( t ) .
(3.2)
Integrating both sides of (3.2) from 0 to T, we have
0 T g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) d t = 0 .
(3.3)
From (3.3), there exists a point ξ [ 0 , T ] such that
g ( ξ , x 1 ( ξ ) , x 1 ( ξ τ ( ξ ) ) , x 1 ( ξ ) ) = 0 .
In view of (H1), we obtain
| x 1 ( ξ ) | D .
Then we have
| x 1 ( t ) | = | x 1 ( ξ ) + ξ t x 1 ( s ) d s | D + ξ t | x 1 ( s ) | d s , t [ ξ , ξ + T ] ,
and
| x 1 ( t ) | = | x 1 ( t T ) | = | x 1 ( ξ ) t T ξ x 1 ( s ) d s | D + t T ξ | x 1 ( s ) | d s , t [ ξ , ξ + T ] .
Combining the above two inequalities, we obtain
| x 1 | = max t [ 0 , T ] | x 1 ( t ) | = max t [ ξ , ξ + T ] | x 1 ( t ) | max t [ ξ , ξ + T ] { D + 1 2 ( ξ t | x 1 ( s ) | d s + t T ξ | x 1 ( s ) | d s ) } D + 1 2 0 T | x 1 ( s ) | d s .
(3.4)
Since ( A x 1 ) ( t ) = x 1 ( t ) c x 1 ( t δ ( t ) ) , we have
( A x 1 ) ( t ) = ( x 1 ( t ) c x 1 ( t δ ( t ) ) ) = x 1 ( t ) c x 1 ( t δ ( t ) ) + c x 1 ( t δ ( t ) ) δ ( t ) = ( A x 1 ) ( t ) + c x 1 ( t δ ( t ) ) δ ( t ) ,
and
( A x 1 ) ( t ) = ( A x 1 ) ( t ) c x 1 ( t δ ( t ) ) δ ( t ) .
By applying Lemma 2.1, we have
| x 1 | = max t [ 0 , T ] | A 1 A x 1 ( t ) | max t [ 0 , T ] | ( A x 1 ) ( t ) c x 1 ( t δ ( t ) ) δ ( t ) | | 1 | c | | φ q ( | x 2 | ) + | c | δ 1 | x 1 | | 1 | c | | ,
where δ 1 = max t [ 0 , T ] | δ ( t ) | . Since | 1 | c | | | c | δ 1 > 0 , then
| x 1 | φ q ( | x 2 | ) | 1 | c | | | c | δ 1 .
(3.5)
On the other hand, from x 2 ( n 3 ) ( 0 ) = x 2 ( n 3 ) ( T ) , there exists a point t 1 [ 0 , T ] such that x 2 ( n 2 ) ( t 1 ) = 0 , which together with the integration of the second equation of (3.1) on interval [ 0 , T ] yields
2 | x 2 ( n 2 ) ( t ) | 2 ( x 2 ( n 2 ) ( t 1 ) + 1 2 0 T | x 2 ( n 1 ) ( t ) | d t ) = λ 0 T | g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + e ( t ) | d t α 1 0 T | x 1 ( t ) | p 1 d t + α 2 0 T | x 1 ( t τ ( t ) ) | p 1 d t + α 3 0 T | x 1 ( t ) | p 1 d t + ( m + | e | ) T ( α 1 + α 2 ) T ( D + 1 2 0 T | x 1 ( t ) | d t ) p 1 + α 3 0 T | x 1 ( t ) | p 1 d t + ( m + | e | ) T = ( α 1 + α 2 ) T 2 p 1 ( 2 D 0 T | x 1 ( t ) | d t + 1 ) p 1 ( 0 T | x 1 ( t ) | d t ) p 1 + α 3 0 T | x 1 ( t ) | p 1 d t + ( m + | e | ) T .
(3.6)
For a given constant δ > 0 , which is only dependent on k > 0 , we have
( 1 + x ) k 1 + ( 1 + k ) x for  x [ 0 , δ ] .
From (3.5) and (3.6), we have
2 | x 2 ( n 2 ) ( t ) | ( α 1 + α 2 ) T 2 p 1 ( 2 D 0 T | x 1 ( t ) | d t + 1 ) p 1 ( 0 T | x 1 ( t ) | d t ) p 1 + α 3 0 T | x 1 ( t ) | p 1 d t + ( m + | e | ) T ( α 1 + α 2 ) T 2 p 1 ( 1 + 2 D p 0 T | x 1 ( t ) | d t ) ( 0 T | x 1 ( t ) | d t ) p 1 + α 3 0 T | x 1 ( t ) | p 1 d t + ( m + | e | ) T ( α 1 + α 2 ) T 2 p 1 T p 1 | x 1 | p 1 + ( α 1 + α 2 ) T D p 2 p 2 T p 2 | x 1 | p 2 + α 3 | x 1 | p 1 T + ( m + | e | ) T ( ( α 1 + α 2 ) T p 2 p 1 + α 3 T ) ( φ q | x 2 | ) p 1 ( | 1 | c | | | c | δ 1 ) p 1 + ( α 1 + α 2 ) T p 1 D p 2 p 2 ( φ q | x 2 | ) p 2 ( | 1 | c | | | c | δ 1 ) p 2 + ( m + | e | ) T = ( ( α 1 + α 2 ) T p 2 p 1 + α 3 T ) | x 2 | ( | 1 | c | | | c | δ 1 ) p 1 + ( α 1 + α 2 ) T p 1 D p 2 p 2 | x 2 | 2 q ( | 1 | c | | | c | δ 1 ) p 2 + ( m + | e | ) T .
(3.7)
Since 0 T φ q ( x 2 ( t ) ) d t = 0 T ( A x 1 ) ( t ) d t = 0 , there exists a point t 2 [ 0 , T ] such that x 2 ( t 2 ) = 0 . From (3.4) and Remark 2.1, we can easily get
| x 2 | 1 2 0 T | x 2 ( t ) | d t T 2 ( 0 T | x 2 ( t ) | 2 d t ) 1 2 T 2 ( T π ) 2 ( n 3 ) ( 0 T | x 2 ( n 2 ) ( t ) | 2 d t ) 1 2 T 2 ( T π ) 2 ( n 3 ) | x 2 ( n 2 ) | .
(3.8)
Combination of (3.7) and (3.8) implies
| x 2 | T 2 ( T π ) 2 ( n 3 ) | x 2 ( n 2 ) | T 2 2 ( T π ) 2 ( n 3 ) [ ( ( α 1 + α 2 ) T p 2 p 1 + α 3 T ) | x 2 | ( | 1 | c | | | c | δ 1 ) p 1 + ( α 1 + α 2 ) T p 1 D p 2 p 2 | x 2 | 2 q ( | 1 | c | | | c | δ 1 ) p 2 ] + T 2 2 ( T π ) 2 ( n 3 ) ( m + | e | ) T .
Since p 2 and [ ( α 1 + α 2 ) T p + 1 + 2 p 1 α 3 T 2 ] 2 p + 1 ( | 1 | c | | | c | δ 1 ) p 1 ( T π ) 2 ( n 3 ) < 1 , there exists a positive constant M 1 (independent of λ) such that
| x 2 | M 1 .
(3.9)
From (3.5) and (3.9), we obtain that
| x 1 | φ q ( | x 2 | ) | 1 | c | | | c | δ 1 M 1 q 1 | 1 | c | | | c | δ 1 : = M 2 .
Hence
| x 1 | D + 1 2 0 T | x 1 ( t ) | d t D + T M 2 2 : = M 3 .
From (3.6), we know
| x 2 ( n 2 ) | 1 2 max | 0 T x 2 ( n 1 ) ( t ) d t | 1 2 0 T | g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + e ( t ) | d t 1 2 [ ( α 1 + α 2 ) T | x 1 | p 1 + α 3 T | x 1 | p 1 + ( m + | e | ) T ] 1 2 [ ( α 1 + α 2 ) T M 3 p 1 + α 3 T M 2 p 1 + ( m + | e | ) T ] : = M n 2 .
From (3.8), we can get
| x 2 | T 2 ( T π ) 2 ( n 4 ) | x 2 ( n 2 ) | T 2 ( T π ) 2 ( n 4 ) M n 2 : = M 4 .
Let M = max { M 1 , M 2 , M 3 , M 4 } + 1 , Ω = { x = ( x 1 , x 2 ) : x < M } and Ω 2 = { x : x Ω Ker L } , then x Ω Ker L
Q N x = 1 T 0 T ( φ q ( x 2 ( t ) ) g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) + e ( t ) ) d t .
If Q N x = 0 , then x 2 ( t ) = 0 , x 1 = M or −M. But if x 1 ( t ) = M , we know
0 = 0 T g ( t , M , M , 0 ) d t .
From assumption (H1), we have M D , which yields a contradiction. Similarly, in the case x 1 = M , we also have Q N x 0 , that is, x Ω Ker L , x Im L . So, conditions (1) and (2) of Lemma 2.2 are both satisfied. Define the isomorphism J : Im Q Ker L as follows:
J ( x 1 , x 2 ) = ( x 2 , x 1 ) .
Let H ( μ , x ) = μ x + ( 1 μ ) J Q N x , ( μ , x ) [ 0 , 1 ] × Ω , then ( μ , x ) ( 0 , 1 ) × ( Ω Ker L ) ,
H ( μ , x ) = ( μ x 1 ( t ) 1 μ T 0 T [ g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) e ( t ) ] d t μ x 2 ( t ) ( 1 μ ) φ q ( x 2 ( t ) ) ) .
We have 0 T e ( t ) d t = 0 and then
H ( μ , x ) = ( μ x 1 ( t ) 1 μ T 0 T [ g ( t , x 1 ( t ) , x 1 ( t τ ( t ) ) , x 1 ( t ) ) ] d t μ x 2 ( t ) ( 1 μ ) φ q ( x 2 ( t ) ) ) , ( μ , x ) ( 0 , 1 ) × ( Ω Ker L ) .
From (H1), it is obvious that x H ( μ , x ) < 0 , ( μ , x ) ( 0 , 1 ) × ( Ω Ker L ) . Hence,
deg { J Q N , Ω Ker L , 0 } = deg { H ( 0 , x ) , Ω Ker L , 0 } = deg { H ( 1 , x ) , Ω Ker L , 0 } = deg { I , Ω Ker L , 0 } 0 .

So, condition (3) of Lemma 2.2 is satisfied. By applying Lemma 2.2, we conclude that equation L x = N x has a solution x = ( x 1 , x 2 ) on Ω ¯ D ( L ) , i.e., (2.2) has a T-periodic solution x 1 ( t ) .

Finally, observe that y 1 ( t ) is not a constant. For if y 1 a (constant), then from (1.4) we have g ( t , a , a , 0 ) e ( t ) 0 , which contradicts the assumption that g ( t , a , a , 0 ) e ( t ) 0 . The proof is complete. □

Similarly, we can get the following result.

Theorem 3.2 Assume that (H2) and (H3) hold, then (1.4) has at least one non-constant T-periodic solution if | 1 | c | | | c | δ 1 > 0 and [ ( α 1 + α 2 ) T p + 1 + 2 p 1 α 3 T 2 ] 2 p + 1 ( | 1 | c | | | c | δ 1 ) p 1 ( T π ) 2 ( n 3 ) < 1 .

We illustrate our results with an example.

Example 3.1 Consider the following neutral functional differential equation
( φ p ( x ( t ) 15 x ( t 1 60 sin 4 t ) ) ) ( 5 ) + 1 3 π x 5 ( t ) + 1 6 π sin x ( t cos 4 t ) + 1 8 π sin 4 t cos x ( t ) = sin 4 t .
(3.10)
Here p = 6 . It is clear that T = π 2 , c = 15 , δ ( t ) = 1 60 sin 4 t , τ ( t ) = cos 4 t , e ( t ) = sin 4 t , δ 1 = max t [ 0 , T ] | 1 15 cos 4 t | = 1 15 , then we can get | 1 | c | | | c | δ 1 = 13 > 0 , g ( t , v 1 , v 2 , v 3 ) = 1 3 π v 1 5 + 1 6 π sin v 2 + 1 8 π cos v 3 sin 4 t , and g ( t , a , a , 0 ) e ( t ) = 1 3 π a 5 + 1 6 π sin a 8 π 1 8 π sin 4 t 0 . Choose D = 3 π such that (H1) holds. Now we consider the assumption (H3), it is easy to see
| g ( t , z 1 , z 2 , z 3 ) | 1 3 π | z 1 | 5 + 1 ,
which means that (H3) holds with α 1 = 1 3 π , α 2 = 0 , α 3 = 0 , m = 1 . Obviously,
[ ( α 1 + α 2 ) T p + 1 + 2 p 1 α 3 T 2 ] 2 p + 1 ( | 1 | c | | | c | δ 1 ) p 1 ( T π ) 2 ( n 3 ) = 1 3 π ( π 2 ) 7 + 0 + 0 2 6 + 1 ( | 1 | c | | c | δ 1 ) 6 1 ( 1 2 ) 2 ( 6 3 ) = π 6 3 × 2 20 × 13 5 < 1 .

By Theorem 3.1, (3.10) has at least one nonconstant π 2 -periodic solution.

Declarations

Acknowledgements

CZB and RJL would like to thank the referee for invaluable comments and insightful suggestions. This work was supported by NSFC project (No. 11271339) and NCET Program (No. 10-0141).

Authors’ Affiliations

(1)
School of Mathematics and Informatics, Henan Polytechnic University, Jiaozuo, China
(2)
School of Mathematics and Statistics, Zhengzhou University, Zhengzhou, China

References

  1. Cao J, He GM: Periodic solutions for higher-order neutral differential equations with several delays. Comput. Math. Appl. 2004, 48: 1491-1503. 10.1016/j.camwa.2004.07.007MathSciNetView ArticleGoogle Scholar
  2. Du B, Guo L, Ge WG, Lu SP: Periodic solutions for generalized Liénard neutral equation with variable parameter. Nonlinear Anal. TMA 2009, 70: 2387-2394. 10.1016/j.na.2008.03.021MathSciNetView ArticleGoogle Scholar
  3. Lu SP: Existence of periodic solutions for a p -Laplacian neutral functional differential equation. Nonlinear Anal. TMA 2009, 70: 231-243. 10.1016/j.na.2007.11.053View ArticleGoogle Scholar
  4. Lu SP, Ge WG: Existence of periodic solutions for a kind of second-order neutral functional differential equation. Appl. Math. Comput. 2004, 157: 433-448. 10.1016/j.amc.2003.08.044MathSciNetView ArticleGoogle Scholar
  5. Ren JL, Cheng ZB: Periodic solutions for generalized high-order neutral differential equation in the critical case. Nonlinear Anal. TMA 2009, 71: 6182-6193. 10.1016/j.na.2009.06.011MathSciNetView ArticleGoogle Scholar
  6. Ren JL, Cheung WS, Cheng ZB: Existence and Lyapunov stability of periodic solutions for generalized higher-order neutral differential equations. Bound. Value Probl. 2011., 2011: Article ID 635767Google Scholar
  7. Wang Q, Dai BX: Three periodic solutions of nonlinear neutral functional differential equations. Nonlinear Anal. RWA 2008, 9: 977-984. 10.1016/j.nonrwa.2007.01.014MathSciNetView ArticleGoogle Scholar
  8. Wang K, Lu SP: On the existence of periodic solutions for a kind of high-order neutral functional differential equation. J. Math. Anal. Appl. 2007, 326: 1161-1173. 10.1016/j.jmaa.2006.03.078MathSciNetView ArticleGoogle Scholar
  9. Wu J, Wang ZC: Two periodic solutions of second-order neutral functional differential equations. J. Math. Anal. Appl. 2007, 329: 677-689. 10.1016/j.jmaa.2006.06.084MathSciNetView ArticleGoogle Scholar
  10. Ren JL, Cheng ZB, Siegmund S: Neutral operator and neutral differential equation. Abstr. Appl. Anal. 2011., 2011: Article ID 969276Google Scholar
  11. Gaines RE, Mawhin JL: Coincidence Degree and Nonlinear Differential Equation. Springer, Berlin; 1977.Google Scholar
  12. Ren JL, Cheng ZB: On high-order delay differential equation. Comput. Math. Appl. 2009, 57: 324-331. 10.1016/j.camwa.2008.10.071MathSciNetView ArticleGoogle Scholar

Copyright

© Cheng and Ren; licensee Springer 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.